Hydraulic performance of a porous pipe irrigation lateral made from recycled tyres - Mohd Soom, Mohd Amin; Islam, Md Fakrul (Universiti Putra Malaysia, 1999)
Irrigation systems are known for their low efficiencies. Efforts must be made to conserve water resource in view of a greater competition from domestic, industrial and other sectors of the economy. Since a micro irrigation system can achieve a very high application efficiency, it should be further explored even for supplemental irrigation in a humid tropical country like Malaysia. Porous pipe irrigation lateral is useful for both surface and subsurface applications. A subsurface installation saves more irrigation water, which would otherwise be lost through surface evaporation. However very little information is now available on the discharge uniformity and operating characteristics of the imported porous pipe currently available locally. This paper presents results of a study on hydraulic characteristics of a type of porous pipes manufactured from recycled tyres. As extruded membrane, the pipe allows water to pass through the pores of the wall at low pressures. The tiny openings are made automatically during the manufacturing process. Since it has regular openings, irrigation is localized in a wetted strip whether it is buried or laid on the ground surface. Pressure-discharge relationship, head loss and friction factor-Reynolds number relationship were evaluated. The porous pipe was tested with various pressure inputs for several different lengths to seek the average rates and discharge uniformity. The pipe acts as a lateral with multiple-emitters. The porous pipe was found to be very sensitive to pressure variation with discharge exponent near 1.0. The pipe friction loss was large since the inner wall was very rough compared to the normal polyethylene laterals and another type of porous pipe made from geotextile.